Behavioral and Neural Pathways Supporting the Development of Prosocial and Risk‐Taking Behavior Across Adolescence. Issue 3 (27th August 2019) - Blankenstein, Neeltje E.; Telzer, Eva H.; Do, Kathy T.; van Duijvenvoorde, Anna C.K.; Crone, Eveline A.
Abstract : This study tested the pathways supporting adolescent development of prosocial and rebellious behavior. Self‐report and structural brain development data were obtained in a three‐wave, longitudinal neuroimaging study (8–29 years, N  = 210 at Wave 3). First, prosocial and rebellious behavior assessed at Wave 3 were positively correlated. Perspective taking and intention to comfort uniquely predicted prosocial behavior, whereas fun seeking (current levels and longitudinal changes) predicted both prosocial and rebellious behaviors. These changes were accompanied by developmental declines in nucleus accumbens and medial prefrontal cortex (MPFC) volumes, but only faster decline of MPFC (faster maturity) related to less rebellious behavior. These findings point toward a possible differential susceptibility marker, fun seeking, as a predictor of both prosocial and rebellious developmental outcomes.